Usia, Pengalaman Hamil Sebelumnya Dengan Perilaku Perawatan Prakonsepsi Pada Wanita Usia Subur Di Kabupaten Kudus - Dinata, Dwi Elysia; Hidayah, Noor; Suwarto, Tri (Universitas Pahlawan Tuanku Tambusai, 2025)
Preconception behaviors are actions taken by women of childbearing age before pregnancy to prepare for a healthy pregnancy. This study aims to analyze the influence of age, previous pregnancy experience, and partner support on preconception behaviors among women of childbearing age in Kudus Regency. The method used was an analytical survey with a cross-sectional approach, involving 100 respondents from 19 community health centers (Puskesmas) in Kudus Regency. Data were collected through a questionnaire that had been tested for validity and reliability. The results showed no significant association between age (p=0.201) and previous pregnancy experience (p=0.290) and preconception behaviors. However, knowledge was shown to have a significant effect on preconception behaviors (p=0.000) with an odds ratio (OR) of 7.639, indicating that women with less knowledge were 7.6 times more likely to have poor preconception behaviors than those with more knowledge. Partner support was also an important factor in shaping preconception behaviors. This study confirms that increasing partner knowledge and support needs to be a focus in efforts to improve preconception behaviors to reduce the risk of high-risk pregnancies and improve the health of mothers and babies.